Force-induced discoloration film with low angle dependence and anti-fatigue performance as well as preparation method and application of force-induced discoloration film

The amorphous photonic crystal film was prepared by modifying nanosilicon dioxide and lifting method and compounded with polydimethylsiloxane, which solved the problem of cumbersome preparation process and low mechanical properties of existing discoloration films, achieving low Force-colored films with angle dependence and fatigue resistance.

CN119391399AActive Publication Date: 2025-02-07WUHAN TEXTILE UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411303840.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-02-07
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The preparation process of existing force-discolored films is cumbersome and takes a long time. The film has low mechanical properties and cannot meet the needs of force-discolored functional materials.

Method used

Nanosilica was prepared by sol-gel method, and modified by silane coupling agent KH570, and a silicon dioxide amorphous photonic crystal film was prepared in combination with pulling method, which was then compounded with polydimethylsiloxane to prepare a Force-colored films with low angle dependence and fatigue resistance.

Benefits of technology

Low angle dependence, high mechanical strength and wear resistance, good thermal stability and chemical stability are achieved, ensuring the efficient performance of the force-induced discolored film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391399A_ABST
    Figure CN119391399A_ABST
Patent Text Reader

Abstract

The invention provides a mechanochromic film with low angle dependence and fatigue resistance as well as a preparation method and application of the mechanochromic film. A silicon dioxide amorphous photonic crystal film is prepared through a sol-gel method, KH570 modification and a Czochralski method; and uniformly coating two surfaces of the film with the PDMS solution to prepare the force-induced discoloration film with low angle dependence and anti-fatigue performance. The nano silicon dioxide photonic crystal is uniform in particle size and good in dispersity in ethanol, so that an amorphous photonic crystal film which is periodically and regularly arranged can be prepared by adopting a Czochralski method, and the amorphous photonic crystal film has low-angle dependence when being observed at different angles under indoor diffuse scattered light; through modification, carbon-carbon double bonds are grafted on the surfaces of silicon dioxide nanoparticles, the silicon dioxide nanoparticles react with hydroxyl and sulfydryl on the surface of PDMS, and chemical bonds are introduced, so that the interface action of the inorganic silicon dioxide nanoparticles and the PDMS is enhanced, and the mechanical property and the anti-fatigue property of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mechanochromic films, and in particular to a mechanochromic film with low angle dependence and anti-fatigue performance, and a preparation method and application thereof. Background Art

[0002] With the rapid development of information technology, information security plays an increasingly important role. How to prevent counterfeiters from using modern technology to forge information, achieve information security and reliability, and reduce the economic losses caused by counterfeit and shoddy products is a huge challenge. Mechanochromic materials are a type of material whose optical properties undergo reversible changes after being stimulated by external mechanical forces. They can perform visual detection and investigation of external forces, and are therefore widely used in anti-counterfeiting, information encryption and other fields. At present, mechanochromic materials are mainly prepared through physical structure regulation (such as photolithography technology, photonic crystal self-assembly), chemical synthesis (designing compounds containing specific mechanochromic group structures) and composite material preparation (combining mechanochromic materials with other materials to enhance the color-changing effect).

[0003] The patent with publication number CN117924970A discloses a photonic crystal structural color material with low angle dependence and a preparation method thereof, wherein a photonic crystal structural color film is prepared by gravity sedimentation, and finally the photonic crystal structural color film is ground, dispersed, ultrasonicated, and dried by colloidal particle self-assembly by redispersion to prepare a photonic crystal structural color material with low angle dependence. The disadvantage of this invention is that the preparation process is relatively cumbersome and time-consuming, and two film-forming conditions are required before and after, and the mechanical properties of the prepared film are not high, so it cannot be applied to mechanochromic functional materials.

[0004] The patent with publication number CN115480324A discloses a method for preparing a smart photonic crystal fabric with a stretch color-changing function. The photonic crystal film is prepared by gravity sedimentation of a suspension of photonic crystal silica nano-microspheres, and then a polydimethylsiloxane solution is coated on the photonic crystal film, and the temperature is increased to cure to obtain a stretch color-changing smart photonic crystal film. After that, a PDMS (polydimethylsiloxane) solution is coated on a black textile fabric, and then the stretch color-changing smart photonic crystal film is placed thereon, and the temperature is increased to cure to obtain a smart photonic crystal textile fabric with a stretch color-changing function. The disadvantage of this invention is that the interfacial force between the stretch color-changing smart photonic crystal film and the fabric is low, and the stretching process easily causes the two to peel off. In addition, during repeated stretching, the color-changing effect of the composite fabric material is uneven, and accurate monitoring of external forces cannot be achieved.

[0005] The patent with the publication number CN118112831A discloses an information presentation method and application based on mechanochromic cholesteric liquid crystal elastomer. By designing the image information into multiple parts with different colors and using mechanochromic cholesteric liquid crystal elastomer as a display, different reading results are presented under different observation conditions, thus realizing multi-level encryption of image information. However, the disadvantage of this invention is that the experimental conditions are relatively strict, and the chiral molecules induce the periodic arrangement of liquid crystal rod-shaped molecules irregularly during the evaporation of the solvent, which makes the color change effect uneven under the action of force, and the information cannot be accurately stored.

[0006] In view of this, it is necessary to design an improved mechanochromic film with low angle dependence and anti-fatigue performance and a preparation method and application thereof to solve the above problems. Summary of the invention

[0007] In view of the defects of the above-mentioned prior art, the purpose of the present invention is to provide a mechanochromic film with low angle dependence and anti-fatigue performance, and a preparation method and application thereof. The silicon dioxide photonic crystals are modified, and an amorphous photonic crystal film is prepared by a pulling method, which is compounded with polydimethylsiloxane to prepare a mechanochromic film with low angle dependence, high mechanical strength and wear resistance, good thermal stability and chemical stability.

[0008] To achieve the above object, the present invention provides a method for preparing a mechanochromic film with low angle dependence and anti-fatigue performance, comprising the following steps:

[0009] S1. Nano-silica was prepared by a sol-gel method and modified with a silane coupling agent KH570 to obtain modified nano-silica;

[0010] S2. A modified nano-silica solution having a predetermined mass concentration is prepared, and a silicon dioxide amorphous photonic crystal film is prepared by a Czochralski method at a constant temperature;

[0011] S3. The polydimethylsiloxane prepolymer and the curing agent are mixed evenly and degassed to obtain a PDMS solution, which is evenly coated on both sides of the silica amorphous photonic crystal film obtained in step S2, and subjected to thermal curing and demolding treatment to obtain a mechanochromic film with low angle dependence and anti-fatigue performance.

[0012] As a further improvement of the present invention, in step S1, the particle size of the nano-silicon dioxide is 190-330 nm.

[0013] As a further improvement of the present invention, in step S2, the concentration of the modified nano-silicon dioxide solution is 3-7 wt%; the thickness of the silicon dioxide amorphous photonic crystal film is 1.0-1.2 mm.

[0014] Furthermore, the constant temperature is 28-32°C.

[0015] The pulling times of the pulling method are 15 to 25 times, the pulling speed is 0.8 to 1.5 mm / s, and the residence time during the pulling process is 55 to 65 seconds.

[0016] As a further improvement of the present invention, in step S3, the mass ratio of the polydimethylsiloxane prepolymer to the curing agent is 10:1.

[0017] Furthermore, the thermal curing temperature is 75-85° C. and the time is 1.5-2 hours.

[0018] Furthermore, the thickness of the mechanochromic film with low angle dependence and anti-fatigue performance is 2.0 to 3.2 mm.

[0019] The present invention also provides a mechanochromic film with low angle dependence and anti-fatigue performance, which is prepared by the above preparation method.

[0020] The above-mentioned mechanochromic film with low angle dependence and anti-fatigue performance is used in the field of information encryption.

[0021] The beneficial effects of the present invention are:

[0022] 1. The present invention provides a mechanochromic film with low angle dependence and fatigue resistance, and a preparation method and application thereof, wherein nano-silicon dioxide is prepared by a sol-gel method, modified by a silane coupling agent KH570, and a modified nano-silicon dioxide is obtained, and a silicon dioxide amorphous photonic crystal film is prepared by a pulling method; a polydimethylsiloxane prepolymer and a curing agent are mixed and degassed to obtain a PDMS solution, which is evenly coated on both sides of the silicon dioxide amorphous photonic crystal film, and subjected to thermal curing and demolding treatment to obtain a mechanochromic film with low angle dependence and fatigue resistance. The present invention uses a sol-gel method to prepare nano-silicon dioxide photonic crystals of different particle sizes. Since the particle size is uniform and the dispersibility is good in ethanol, a periodically regularly arranged amorphous photonic crystal film can be prepared at a certain temperature with a hydrophilic glass slide as the substrate and at a uniform pulling speed, so that it has low angle dependence when observed at different angles under indoor diffuse scattered light.

[0023] 2. Silica was modified with silane coupling agent KH570, and carbon-carbon double bonds were grafted on the surface of silica nanoparticles to make them react with hydroxyl and thiol groups on the surface of PDMS, introducing chemical bonds to enhance the interface between inorganic silica nanoparticles and PDMS, thereby improving the mechanical properties and fatigue resistance of the material. In addition, the periodic structure of silica can deform and recover synchronously with the PDMS matrix, so that the color and information of the material can change reversibly. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the PDMS / modified SiO2 / PDMS "sandwich" film structure prepared by the present invention.

[0025] Figure 2 Schematic diagram of the preparation of nano-silica.

[0026] Figure 3 Schematic diagram of the modification principle of nano-silica.

[0027] Figure 4 Scanning electron microscope images of nano-silicon dioxide particles of different particle sizes prepared in Examples 1-3 of the present invention.

[0028] Figure 5 This is a particle size distribution diagram of nano-silicon dioxide particles with different particle sizes prepared in Examples 1-3 of the present invention.

[0029] Figure 6 This is a relevant characterization diagram of the nano-silica microspheres prepared in Example 1 of the present invention.

[0030] Figure 7 These are digital photos of the silicon dioxide amorphous photonic crystal films prepared in Examples 1-3 of the present invention under different diffuse light angles.

[0031] Figure 8 The stress-strain curves of the mechanochromic films prepared in Example 1 of the present invention and Comparative Examples 1-2.

[0032] Fig. 9 The cyclic stretching curves of the mechanochromic films prepared in Example 1 of the present invention and Comparative Examples 1-2.

[0033] Fig.10 These are diagrams showing the information “display” and “erasure” effects of the mechanochromic film prepared in Example 1 of the present invention under different strains. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0035] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.

[0036] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0037] The present invention provides a method for preparing a mechanochromic film with low angle dependence and anti-fatigue performance, such as Figure 1 As shown, the following steps are included:

[0038] S1. Prepare nano-silica by sol-gel method, and modify it with silane coupling agent KH570 to obtain modified nano-silica.

[0039] Specifically, the sol-gel method is used to prepare nano-silicon dioxide with a particle size of 190 to 330 nm. Figure 2 As shown, prepare reaction liquid A: prepare an ammonia solution with a concentration of 7-9%, mix it with anhydrous ethanol in a volume ratio of 1:2, and stir it in a water bath at 25-35°C for 10-15 minutes. Prepare reaction liquid B: prepare an anhydrous ethanol solution containing 16-20% tetraethoxysilane at room temperature, and stir it magnetically for 10-15 minutes. Quickly pour reaction liquid B into liquid A, and the volume ratio of reaction liquid A to reaction liquid B is (1-2):1; stir and react for 4.5-5.5 hours. After the reaction is completed, the product is centrifuged, washed, dried, and ground to obtain nano-silicon dioxide powder. Nano-silicon dioxide with different particle sizes can be prepared by adjusting the amount of ammonia water.

[0040] Modification with silane coupling agent KH570, prepare reaction liquid A: mix ethanol and deionized water in a volume ratio of 1:1 to prepare an ethanol solution, and ultrasonically mix the dried nano-SiO2 and ethanol solution in a solid-liquid ratio of 1g:20mL. Prepare reaction liquid B: mix ethanol and deionized water in a volume ratio of 18:2 to obtain an alcohol-water medium, adjust the solution pH to 4.5-5.5 with oxalic acid, add 5% KH570 by volume, and stir at room temperature for 1-1.5h. Add reaction liquid A to reaction liquid B, and heat to 65-75℃ at the same time, and react at this temperature for 5-7h. Cool to room temperature, centrifuge, wash, dry, and fully grind to obtain modified nano-silica powder.

[0041] like Figure 3 As shown in the figure, the modification principle of nano-silica is to graft carbon-carbon double bonds on the surface of silica nanoparticles, react with hydroxyl and thiol groups on the surface of PDMS, introduce chemical bonds, and enhance the interfacial force between silica and polydimethylsiloxane. At the same time, the periodic structure of silica nanoparticles can be better reset after repeated deformation, thus having better color changeability and stronger anti-fatigue performance.

[0042] S2. Prepare a modified nano-silica solution with a predetermined mass concentration, and prepare a silicon dioxide amorphous photonic crystal film by a pulling method at a constant temperature.

[0043] Specifically, the concentration of the modified nano-silicon dioxide solution is 3-7wt%; the constant temperature is 28-32°C.

[0044] The pulling times of the pulling method are 15 to 25 times, the pulling speed is 0.8 to 1.5 mm / s, and the residence time during the pulling process is 55 to 65 seconds; the thickness of the obtained silicon dioxide amorphous photonic crystal film is 1.0 to 1.2 mm.

[0045] The Czochralski method for preparing photonic crystal films is beneficial to improving the uniformity of color change and the independence of observation angle.

[0046] S3. The polydimethylsiloxane prepolymer and the curing agent are mixed evenly and degassed to obtain a PDMS solution, which is evenly coated on both sides of the silica amorphous photonic crystal film obtained in step S2, and subjected to thermal curing and demolding treatment to obtain a mechanochromic film with low angle dependence and anti-fatigue properties.

[0047] Specifically, the polydimethylsiloxane prepolymer and the curing agent are mechanically stirred and evenly mixed in a mass ratio of 10:1, and degassed in a vacuum oven, and then evenly coated on the surface of the silicon dioxide amorphous photonic crystal, thermally cured in an oven at 75-85°C for 1.5-2 hours, and then demolded to prepare a PDMS / SiO2 film; then the PDMS solution is evenly coated on the reverse side again, thermally cured and demolded to prepare a mechanochromic film with low angle dependence and anti-fatigue performance having a PDMS / modified SiO2 / PDMS "sandwich" structure, with a thickness of 2.0-3.2 mm.

[0048] The preparation method of the mechanochromic film with low angle dependence and anti-fatigue performance provided by the present invention is described below in conjunction with specific embodiments.

[0049] Example 1

[0050] Embodiment 1 provides a method for preparing a mechanochromic film with low angle dependence and anti-fatigue performance, comprising the following steps:

[0051] S1. Prepare nano-silica by sol-gel method, specifically, prepare reaction liquid A: add 2mL ammonia water, 23mL deionized water, 50mL anhydrous ethanol to a 250mL round-bottom flask, and stir in a 30℃ water bath at a speed of 1500rap / min for 10min. Prepare reaction liquid B: add 9mL tetraethoxysilane and 41mL anhydrous ethanol to a 100mL beaker at room temperature, and stir magnetically for 10 minutes. Quickly pour reaction liquid B into liquid A, adjust the speed to 800r / min after 2min, and stir the reaction for 5h. After the reaction, centrifuge the product for 8min with a centrifuge at a centrifugal speed of 11000r / min. After the centrifugation, remove the supernatant, pour deionized water, and centrifuge again after ultrasonic homogenization. Then, wash with water twice and alcohol twice in the same way to remove ammonia water. Finally, dry the product in an oven at 80℃, and then grind it with a mortar to obtain a nano-silica white powder with a particle size of 330nm.

[0052] Modification with silane coupling agent KH570, preparation of reaction liquid A: take 1g of dried nano-SiO2 and mix with (10mL ethanol + 10mL deionized water), ultrasonic for 20min. Preparation of reaction liquid B: add 18mL ethanol and 2mL deionized water to a 50mL beaker, adjust pH to 5 with oxalic acid, take 1mL KH570 with a pipette and add it to the weakly acidic alcohol-water medium, stir at room temperature for 1h. Add reaction liquid A to reaction liquid B, raise the temperature to 70℃ at the same time, and react at this temperature for 6h. Cool to room temperature, centrifuge at 1000r / min for 5min, wash with anhydrous ethanol ultrasonic dispersion 5 times, and finally dry the product in an oven at 80℃, and then fully grind it with a mortar to obtain the modified nano-silica powder.

[0053] S2. Prepare a modified nano-silica solution with a mass concentration of 5wt%, and prepare a silica amorphous photonic crystal film by a pulling method at 30°C. Specifically, immerse a hydrophilic glass slide in the photonic crystal solution at a speed of 1mm / s for 60 seconds, and then take it out at the same rate for 20 times, thereby preparing a silica amorphous photonic crystal film with low angle dependence.

[0054] S3. The polydimethylsiloxane prepolymer and the curing agent are evenly mixed by mechanical stirring at a mass ratio of 10:1, and degassed in a vacuum oven. Then, they are evenly coated on the surface of the silicon dioxide amorphous photonic crystal, thermally cured in an oven at 80°C for 2 hours, and then demolded to prepare a PDMS / SiO2 film. The PDMS solution is then evenly coated on the reverse side again, thermally cured at 80°C, and then demolded to obtain a PDMS / modified SiO2 / PDMS film with a thickness of 2.1 mm.

[0055] Example 2

[0056] Example 2 provides a method for preparing a mechanochromic film with low angle dependence and anti-fatigue performance. Compared with Example 1, the only difference is that the amount of ammonia water used is 4 mL, and the particle size of the obtained nano-silica is 290 nm. The other experimental parameters and conditions are basically the same as those in Example 1 and will not be repeated here.

[0057] Example 3

[0058] Example 3 provides a method for preparing a mechanochromic film with low angle dependence and anti-fatigue performance. Compared with Example 1, the only difference is that the amount of ammonia water used is 6 mL, and the particle size of the obtained nano-silica is 190 nm. The other experimental parameters and conditions are basically the same as those in Example 1 and will not be repeated here.

[0059] Comparative Example 1

[0060] Comparative Example 1 provides a method for preparing a mechanochromic film with low angle dependence and anti-fatigue performance. Compared with Example 1, the only difference is that a pure PDMS film of the same thickness is prepared. Other experimental parameters and conditions are basically the same as those in Example 1 and will not be repeated here.

[0061] Comparative Example 2

[0062] Comparative Example 2 provides a method for preparing a mechanochromic film with low angle dependence and anti-fatigue performance. Compared with Example 1, the only difference is that the nano-silica is not modified with the silane coupling agent KH570 to obtain the PDMS / SiO2 / PDMS film. The other experimental parameters and conditions are basically the same as those in Example 1 and will not be repeated here.

[0063] Figure 4 The scanning electron microscope images of nano-SiO2 particles of different particle sizes prepared in Examples 1-3 of the present invention, the particle sizes from left to right are (a) 330nm, (b) 290nm, and (c) 190nm. It can be seen that with the increase of the amount of ammonia water (the amount of ammonia water used from left to right is 2mL, 4mL, and 6mL), the particle size of the nano-SiO2 particles gradually decreases, and the surface of the microspheres is very smooth, without extrusion deformation, and is in a good spherical shape.

[0064] Figure 5 The particle size distribution diagram of nano-SiO2 particles with different particle sizes prepared in Examples 1 to 3 of the present invention shows that the particle size of SiO2 microspheres is normally distributed with a narrow distribution range, indicating that SiO2 microspheres have good dispersibility in anhydrous ethanol and no agglomeration.

[0065] Figure 6The relevant characterization diagrams of the nano-silica microspheres prepared in Example 1 of the present invention are as follows: (a) is the FT-IR of SiO2 microspheres before and after high-temperature calcination; (b) is the FT-IR of SiO2 microspheres before and after modification; (c) is the XRD diagram of SiO2 nano-microspheres. (a) It can be seen that after calcination, at 2920 cm -1 (-CH3- stretching vibration absorption peak) and 2850cm -1 (-CH2- stretching vibration absorption peak) disappears, indicating that calcination removes organic matter on the surface of silica. (b) It can be seen that after SiO2 modification, the absorption peak at 1860 cm -1 (-C=O vibration absorption peak), 2920cm -1 / 2850cm -1 (-CH3- / -CH2- vibration absorption peak), it can be concluded that KH570-SiO2 was successfully prepared. (c) It can be seen that the silica powder before and after modification has only one broad diffraction peak located near 23.5°, indicating that the synthesized SiO2 belongs to an amorphous structure.

[0066] Figure 7 These are digital photos of the silicon dioxide amorphous photonic crystal films prepared in Examples 1-3 of the present invention under different angles of diffuse light, where Sample 1, Sample 2, and Sample 3 represent structural color films prepared from SiO2 with particle sizes of 330nm, 190nm, and 290nm, respectively. It can be seen that the color of the structural color films prepared from SiO2 with different particle sizes does not change with the change of angle under indoor diffuse light.

[0067] Figure 8 The stress-strain curves of the films prepared by Example 1 of the present invention and Comparative Examples 1-2 show that the mechanical properties of the PDMS / modified SiO2 / PDMS film prepared by modified SiO2 are better than those of the unmodified SiO2 composite film, the fracture strength is close to that of the pure PDMS film, and the fracture strain has only a small decrease.

[0068] Fig. 9 The cyclic stretching curves of the films prepared by Example 1 of the present invention and Comparative Examples 1-2, wherein (a) and (b) are the cyclic stretching curves of the films prepared by Comparative Examples 1 and 2, respectively, and (c) is the cyclic stretching curve of the film prepared by Example 1. It can be concluded that the carbon-carbon double bonds grafted on the surface of the modified SiO2 nanoparticles can react with the hydroxyl and thiol groups on the surface of PDMS to introduce covalent bonds, thereby enhancing the interface effect between the inorganic silica nanoparticles and PDMS, reducing its energy dissipation and improving the elastic recovery performance of the material.

[0069] Fig.10The diagram of the information "display" and "erasing" effects of the film prepared in Example 1 of the present invention under different strains shows that after the PDMS / modified SiO2 / PDMS film is stretched, under different tensile strains (ε=0-72%), the periodic arrangement of the modified silica changes, the light transmittance changes, and the information can be displayed. After the external force is removed, the information is erased, and the periodic structure of silica can deform and recover synchronously with the PDMS matrix, so that the color and information of the material can change reversibly.

[0070] In summary, the present invention uses a sol-gel method to prepare nano-silicon dioxide photonic crystals of different particle sizes. Since the particle size is uniform and the dispersibility in ethanol is good, it is possible to prepare a periodically regularly arranged amorphous photonic crystal film at a certain temperature, using a hydrophilic glass slide as a substrate, and using a universal tensile testing machine at a certain pulling speed, so that it has low angle dependence when observed at different angles under indoor diffuse scattered light. Silane coupling agent KH570 is used to modify silicon dioxide, and carbon-carbon double bonds are grafted on the surface of silicon dioxide nanoparticles to react with hydroxyl and thiol groups on the surface of PDMS, introduce chemical bonds, and enhance the interface between inorganic silicon dioxide nanoparticles and PDMS, thereby improving the mechanical properties and fatigue resistance of the material, and the silicon dioxide periodic structure can be deformed and recovered synchronously with the PDMS matrix, so that the color and information of the material can be reversibly changed.

[0071] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a mechanochromic film with low angle dependence and anti-fatigue performance, characterized in that: The following steps are involved: S1. Nano-silica was prepared by a sol-gel method and modified with a silane coupling agent KH570 to obtain modified nano-silica; S2. A modified nano-silica solution having a predetermined mass concentration is prepared, and a silicon dioxide amorphous photonic crystal film is prepared by a Czochralski method at a constant temperature; S3. The polydimethylsiloxane prepolymer and the curing agent are mixed evenly and degassed to obtain a PDMS solution, which is evenly coated on both sides of the silica amorphous photonic crystal film prepared in step S2, and subjected to thermal curing and demolding treatment to obtain a mechanochromic film with low angle dependence and anti-fatigue performance.

2. The method for preparing a mechanochromic film with low angle dependence and anti-fatigue performance according to claim 1, characterized in that: In step S1, the particle size of the nano-silicon dioxide is 190-330 nm.

3. The method for preparing a mechanochromic film with low angle dependence and anti-fatigue performance according to claim 1, characterized in that: In step S2, the concentration of the modified nano-silicon dioxide solution is 3-7 wt%; the thickness of the silicon dioxide amorphous photonic crystal film is 1.0-1.2 mm.

4. The method for preparing a mechanochromic film with low angle dependence and anti-fatigue performance according to claim 3, characterized in that: In step S2, the constant temperature is 28-32°C.

5. The method for preparing a mechanochromic film with low angle dependence and anti-fatigue performance according to claim 4, characterized in that: In step S2, the pulling method is performed 15 to 25 times, the pulling speed is 0.8 to 1.5 mm / s, and the residence time during the pulling process is 55 to 65 s.

6. The method for preparing a mechanochromic film with low angle dependence and anti-fatigue performance according to claim 1, characterized in that: In step S3, the mass ratio of the polydimethylsiloxane prepolymer to the curing agent is 10:

1.

7. The method for preparing a mechanochromic film with low angle dependence and anti-fatigue performance according to claim 6, characterized in that: The temperature of the thermal curing is 75-85° C. and the time is 1.5-2 hours.

8. The method for preparing a mechanochromic film with low angle dependence and fatigue resistance according to claim 7, characterized in that: The thickness of the mechanochromic film with low angle dependence and anti-fatigue performance is 2.0 to 3.2 mm.

9. A mechanochromic film with low angle dependence and fatigue resistance, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.

10. Application of a mechanochromic film with low angle dependence and fatigue resistance, characterized in that: The mechanochromic film with low angle dependence and fatigue resistance as claimed in claim 9 is used in the field of information encryption.

Citation Information

Patent Citations

  • Photonic crystal structure color material with low angle dependence and preparation method thereof

    CN117924970A

  • Information presentation method based on force-induced color change cholesteric liquid crystal elastomer and application

    CN118112831A

  • Non-angle-dependent structural color soft driver and preparation method and application thereof

    CN114815316A

  • Modified ultraviolet curing acrylic resin paint and preparation method thereof

    CN115340810A

  • Preparation method of intelligent photonic crystal fabric with stretching color changing function

    CN115480324A